Pengembangan Sistem Informasi E-CRM Berbasis Website pada Dinikoe Keramik - Farhani Ayu Amalina; Ismiarta Aknuranda; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dinikoe Keramik is one of UMKM that produce and sell various kinds of souvenir made of ceramic. One of the most important part of the UMKM is the process of selling and retaining customers. The existing sales process at UMKM held by phone call or store visiting. Thus, that existing sales process has disadvantages complaint from the customer is one of that disadvantages that happened oftentimes, that complaint came because of the customers didn't get the fast response about the product and order questions. Moreover, there's no integration information system so that business process in the organization run slowly. Therefore, Dinikoe Keramik needs an information system that using Customer Relationship Management (CRM) strategy to maintain customer loyalty. The system is builded by using Waterfall method which have some processes such as business process analysis and requirements, design, system implementation, and testing. To fulfill the customer's needs, 16 functional needs and 2 nonfunctional needs used as the basic of system development process. The result of system testing showed that the system could meet the user's functional needs, run on the type and version of web browsers tested by the SortSite tool, and effectiveness testing generate 97% score at customer's user group and 83% at sales staff's user group.